Planning Evaluasi Pembelajaran Menggunakan Aplikasi Al-Qur’an Kemenag - Kusumawati; Idris Tumnenggung, Ham (Shofanah Media Berkah, 2025)
The research method uses analytical descriptive with triangulation actions carried out so as to determine the final results of the analysis as follows; 1) Preparation and Observation, attendance, RPS, theoretical basis, student ability data and explaining the Qur'an as a source of Islamic law. 2) Taking data from the mid-term exam summative test. 3) giving the name of the surah and verses to the specified surah number. 4) looking for the mention of the word al-Qur'an in juz 1-5. 5) looking for the mention of the word al-Qur'an in the specified QS. 6) giving a questionnaire for Learning Evaluation Planning Using the Ministry of Religion's Al-Qur'an Application. With the results of the study, as many as 4 (2.6%) respondents always read the Qur'an on mobile applications with various branch markets, 9 (13.8%) often, 21 (32.3%) sometimes, 7 (10.7%) never read the Qur'an using the application. A total of 12 (18.5%) respondents always chose to use applications other than the Ministry of Religious Affairs' Al-Qur'an as learning media, 14 (21.5%) often, 31 (47.6%) sometimes, 5 (7.6%) respondents never chose to use applications other than the Ministry of Religious Affairs' Al-Qur'an as learning media. The obstacles in using the Al-Qur'an application were not too difficult due to the respondents' basic study of informatics engineering, the use of applications other than the Ministry of Religious Affairs' Al-Qur'an application in Islamic religious education learning, respondents used Pro Muslim, Al-Qur'an Indonesia, NU online, and Google Browser.